Analysis of Factors that Drive Startup Growth in Indonesia - Chai, Napat; Tan, Marcus; Rocha, Thiago (Journal of Loomingulisus ja Innovatsioon, 2025)
The rapid growth of startups in Indonesia has become a significant driver of economic development, especially in the digital and tech sectors. Despite the increasing number of startups, understanding the factors that contribute to their growth remains a complex challenge. This study aims to analyze key drivers of startup success in Indonesia, focusing on external factors, internal strategies, and market conditions that influence their scalability. The primary objective of this research is to identify and analyze the critical factors that contribute to the growth of startups in Indonesia. It seeks to explore the role of innovation, funding, government policies, market demand, and networking opportunities in driving the expansion of new ventures. This study uses a mixed-methods approach, combining quantitative surveys of 100 startup founders and qualitative interviews with industry experts. Data analysis is conducted using descriptive statistics and thematic analysis to identify recurring themes and patterns in the factors that influence startup growth. The findings indicate that access to funding, government support, and a robust market demand are the most influential factors in driving startup growth. Additionally, networking and mentorship play critical roles in providing startups with necessary resources and strategic insights. Startups in the tech and e-commerce sectors show higher growth potential compared to those in other industries. The growth of startups in Indonesia is primarily driven by a combination of financial resources, strategic government initiatives, and market opportunities.